Experimental Research of High-Energy Capabilities of Material Recognition by Dual-Energy Method for the Low- Dose Radiation - Abashkin A.; Osipov S. P. Sergey Pavlovich; Chakhlov S. V. Sergey Vladimirovich; Stein A. M. Aleksandr Mikhailovich (2016, 2016)
Title screen